(untitled) (Bangladesh Pharmaceutical Journal, 2023)
p-coumaric acid, commonly referred to as 4-hydroxycinnamic acid, is a phenolic acid, which has been subjected to much research in recognition of its beneficial properties against several diseases and its widespread distribution in the plant kingdom. This compound can be found in the free-state or coupled with other molecules in nature. It has demonstrated prospective pharmacological effects including antiproliferative, nephroprotective, neuroprotective, antioxidant and antimicrobial effects in addition to other biological properties through numerous in vivo, in vitro and clinical studies. This review reported a short summary on p-coumaric acid to provide fundamental information in its biosynthesis, plant sources, and pharmacological effects which may help in future research and development of novel therapeutics. Bangladesh Pharmaceutical Journal 26(2): 185-194, 2023 (July)